OVERSIGHT OF COMMERCIAL COMPANIES BETWEEN CORPORATE LAW AND TAX LEGISLATION - Dhannoon, Mohammed Saud (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2025)
Objective:  This research deals with the study of the control of commercial companies from a dual perspective that combines commercial law and tax legislation, with the aim of analyzing the effectiveness of the legal system in controlling the performance of companies and ensuring their compliance with the legislation in force. Method: The research is based on the legal analytical approach, and is divided into three main chapters: the first chapter deals with the theoretical framework of control, in terms of concept, types, and objectives; the second chapter focuses on legal control under the Companies Law, through incorporation, the role of the commercial register, and the responsibilities of management; while the third chapter deals with tax control, its tools, and its impact on companies, indicating the complementary relationship between the legal and tax systems. Results: The research concluded that it is necessary to develop control tools, strengthen institutional coordination between legal and tax authorities, and impose clear legal obligations on commercial companies, in order to ensure a balance between freedom of investment and the interest of the state in tax collection and regulatory control. Novelty: The importance of control is highlighted in light of the growing economic activities and the multiplicity of forms of companies, which requires accurate and effective control mechanisms capable of ensuring transparency, integrity, and combating financial and administrative corruption.